Perubahan Kesiapsiagaan Masyarakat DAS Beringin Kota Semarang dalam Menghadapi Ancaman Banjir Bandang - Afrizal Novan Nurromansyah; Jawoto Sih Setyono (Department of Urban and Regional Planning, Diponegoro University, 2014)
In 2010 a large flash flood happened in the region of Beringin watershed in Semarang. After the disaster, The Government of Semarang City with the community ran the program namely Flood Early Warning System (FEWS) conducted in the area of Beringin watershed. One of priority actions is strengthening for disaster preparedness. This research aims to describe the change of preparedness efforts that occurs after running the program. The research uses a qualitative approach. A method of sampling is purposive sampling. The technique of data analysis use descriptive qualitative analysis. The results of research show that the change occurring in understanding disaster preparedness efforts, mobilization of resources, flash flood early warning system and preparedness planning. Disaster understanding changes in sources of information on the aspect of knowledge, and the aspect of the act of disaster mitigation paradigm. On the preparedness efforts related to the mobilization of resources, the change happens on aspect of the availability of the disaster team, command procedures, the role of institutional aspects, the aspect of the institutional structure, the aspect of communication and coordination of the scheme, the agreement the use of tools and management of communication to the outside and in the region.